From ‘daughter of the wheel’ to ‘beautiful vigorous and healthy creature’: Maria, “A enjeitada”, by Maria Amália Vaz de Carvalho - de Souza Mariano, Juliana (2021)
In this article, we analyze “A enjeitada”, from Serões no campo. This is Maria Amália Vaz de Carvalho’s first book of narratives, published in 1877. By analyzing this novel, we intend to think about Portuguese family structures of the period, as well as to understand a little more about the author’s perspective on discussions in vogue in the period, such as the clashes between Romanticism and Realism, the social roles of women, the right to education, the class struggle, motherhood, the confrontation between reason and dream, and the role of religion.